Potential impact of biochar and organic fertilizer application on morphology, productivity and biochemical composition of onion plants - Ghuncha Kamal Tofiq; Hawar Sleman Halshoy; Hanar Jamal Mohammed; Shwana Ahmed Braim (Cogent Food & Agriculture)
Organic production is driven by global demand, necessitating the exploration and implementation of novel agricultural approaches. To enhance this approach, many natural resources are available. Thus, this study aims to evaluate the effects of biochar (BiCh) and organic fertilizer (OrF) to improve the nutrient quality and productivity of onion (Allium cepa) plants. The consumption of fresh onion plants offers numerous health benefits due to their rich nutrient content. This study investigates the impact of BiCh (0, 4, and 8 ton/ha) and OrF (0, 10, and 20 L/ha) on the enhancement of root volume, morphology, yield, and biochemical attributes of onion plants. OrF at 10 L/ha significantly influences leaf weight (16.00 g), antioxidants in the bulb (4.22 μg/g), nitrogen in the leaf (2.63%), phosphorus in the leaf (0.31%), and bulbs (0.26%). Moreover, combining BiCh at 4 ton/ha with OrF at 10 L/ha positively affects most characteristics. Applying BiCh at 4 ton/ha did not impact the plant. In contrast, the control group exhibited the lowest values in key parameters, emphasizing the importance of BiCh and OrF applications in enhancing onion plant performance. These findings provide practical insights for farmers aiming to optimize organic production and contribute to economically sustainable practices in high tunnel environments.